Pre-treatment effects on the composition and functionalities of pigeon pea seed ingredients - Locali-Pereira, Adilson Roberto [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Rabesona, Hanitra; Laurent, Sophie; Meynier, Anne; Kermarrec, Alice; Birault, Lucie; Geairon, Audrey; Le Gall, Sophie; Thoulouze, Loric; Solé-Jamault, Véronique; Berton-Carabin, Claire; et al. (Elsevier, 2024)
Soaking and boiling can improve the digestibility of seeds by reducing anti-nutritional factors and the hard-to-cook phenomenon. The use of pre-treated seeds in protein fractionation is thus of interest for the development of protein-rich ingredients. In this work, soaked and soaked-boiled seeds were applied prior to aqueous fractionation of pigeon pea proteins. Pre-treatments impact the particle size distribution in the flours, with boiling leading to aggregate formation (>1000 μm) due to starch gelatinization. The soaked-boiled flour showed a lower lipid content, higher content in soluble polysaccharides, and loss of proteins with low molecular weight compared to the control. The use of soaked-boiled seeds for protein fractionation reduced trypsin inhibitor activity by 95%, demonstrating a positive effect in improving nutritional quality. Protein fractionation also resulted in a 3-fold accumulation of lipids, and the mannose content, notably, doubled in protein concentrates compared to their flour counterparts. A lower intensity of tryptophan fluorescence emission was observed in protein concentrates, which may be related to chemical degradation or interactions with other molecules. The protein concentrate from soaked-boiled seeds exhibited higher emulsion stabilization properties compared to the others protein concentrates. The decrease in foaming properties caused by the soaking can be attributed to the leaching of minor compounds that also act as foaming agents, such as saponins. This work brings new insights into the effects of soaking and boiling-based pre-treatments on the composition of pulse protein ingredients, and in turn, on their techno-functionalities as exemplified with their emulsifying, foaming and gelling properties.
Keywords: Alternative protein; Boiling; Cajanus cajan; Plant-based protein; Pulse crop; Soaking